Rickettsioses as major etiologies of unrecognized acute febrile illness, Sabah, East Malaysia - Grigg, Matthew J. (2021)
Orientia tsutsugamushi, spotted fever group rickettsioses, and typhus group rickettsioses (TGR) are reemerging causes of acute febrile illness (AFI) in Southeast Asia. To further delineate extent, we enrolled patients >4 weeks of age with nonmalarial AFI in Sabah, Malaysia, during 2013-2015. We confirmed rickettsioses (past or acute, IgG titer >160) in 126/354 (36%) patients. We confirmed acute rickettsioses (paired 4-fold IgG titer rise to >160) in 38/145 (26%) patients: 23 O. tsutsugamushi, 9 spotted fever group, 4 TGR, 1 O. tsutsugamushi/spotted fever group, and 1 O. tsutsugamushi/TGR. PCR results were positive in 11/319 (3%) patients. Confirmed rickettsioses were more common in male adults; agricultural/plantation work and recent forest exposure were risk factors. Dizziness and acute hearing loss but not eschars were reported more often with acute rickettsioses. Only 2 patients were treated with doxycycline. Acute rickettsioses are common (>26%), underrecognized, and untreated etiologies of AFI in East Malaysia; empirical doxycycline treatment should be considered.